Plant-Based Oral Nutrition Supplementation Promotes Weight Gain in Patient Status-Post Burn Injury. (14th June 2022) - Bailey, Melissa; Ray, Susan; Narayanaswamy, Deepa; Homer, MeaLenea
Abstract: Objectives: Burn nutrition therapy is intended to mitigate some but not all the catabolism of lean body mass seen in severe burn patients. Hypermetabolism is a chronic problem and can last 2–3 years after injury. Vegetarian and non-vegetarian diets have been found to be comparable in the outcomes and nutritional status of patients 60 days post burn. Methods: This case report documents a hypermetabolic burn patient's transition to an oral diet with use of a plant-based pea protein enteral formula (PPEF) for maintenance of weight and nutritional status. Patient was a 52 year old male with no significant past medical history who presented with 55% total body surface area burn, admitted to the burn ICU on 1/2/21. Patient was placed on a dairy-based immunomodulating formula as exclusive enteral nutrition with an additional protein modular upon admission. On 2/23/21, patient was transitioned to a regular, vegetarian diet, per patient dietary preference, with supplemental enteral nutrition (EN) and able to meet 12% of calorie needs orally (PO). A standard, intact PPEF oral nutrition supplement (ONS) was added three times daily on 2/25/21. On 3/8/21, EN was held to allow for appetite stimulation. Patient consumed minimal amounts PO and only 1–2 ONS per day, therefore, the dietitian changed the ONS to a standard, intact calorically dense PPEF. Patient consumed 2–4 calorically dense PPEF ONS per day for the next 7 weeks until discharge. This accounted for 32–82.5% of patient's total calorie needs and 23.3–65.5% of total protein needs while on oral diet. Results: During hospitalization, the patient gained 5.3kg while on oral diet and PPEF ONS. Patient was then discharged (d/c) to a rehab facility on 4/23/21, where PPEF ONS was unavailable. Patient was placed on a standard intact dairy based ONS. Patient was readmitted to the hospital on 5/14/21 with weight loss of 2.7kg. Patient was placed back on standard, intact calorically dense PPEF ONS during readmission, where he drank 1–2 per day until d/c back to rehab facility 5 days later. Conclusions: This case report demonstrates that PPEF ONS was a viable alternative nutritional therapy to promote weight gain in this burn patient. A prospective study looking at objective measures, such as nutritional status and inflammatory markers, in burn patients on plant-based enteral formulas in the acute care setting is necessary. Funding Sources: N/A.